WORKING OUT OF TECHNOLOGY OF TINCTURE ARTICHOKE - Namozov, F.Sh.; Abdujabborov , A.A. (Educational Research in Universal Sciences, 2023)
In this experimental part, we obtained conclusions on the improvement of the technological processes of the tincture obtained from the herbal of the prickly artichoke and the creation of an efficient method convenient for production plants.